(untitled) (AYUSHDHARA, 2017)
Wide description is available in Ayurvedic classics regarding various surgical instruments (Yantra, Shastra) used in different branches of Ayurveda for carrying out clinical examination; medical and operative procedures. Hasta (Hand) is considered as the Pradhantamam yantra because surgical instruments are in many ways simply extension of human hand. Surgical instruments such as forceps, dilators, speculums, needles, lancets etc are similar to the 101Yantras and 20 Shastras mentioned in Ayurveda e.g., Samdansha Yantra, Naadi Yantra, Shalaka Yantra, Mandalagra Shastra, Vetasapatra Shastra, Suchi, Shararimukha Shastra etc. To perform various procedures in Stree Roga and Prasuti Tantra , use of blunt and sharp instruments are described in detail. Most of the modern surgical instruments are only slight modifications of the instruments used by ancient Hindu surgeons. In this article we have discussed about those Yantras (Blunt instruments) and Shastras (Sharp instruments) which are mentioned in Stree Roga and Prasuti Tantra and their counterparts in modern Obstetrics and Gynecology.